A RUPTURA SOCIAL INFANTOJUVENIL E SUA INFERÊNCIA NAS REPRESENTAÇÕES DE CONSELHEIROS TUTELARES - Garbin, Cléa Adas Saliba [UNESP]; Bordin, Danielle; Fadel, Cristina Berger; Garbin, Artênio José Ísper [UNESP]; Saliba, Nemre Adas [UNESP] (Fundação Oswaldo Cruz, Escola Politécnica de Saúde Joaquim Venâncio, 2017)
Abstract This qualitative study introduces the theme of the tutelary counselors' representations to broaden the understanding of these social players' universe and to get to know their implications regarding the dynamics of their work process. The study was conducted in the city of Coronel Vivida, in the state of Paraná, Brazil, in 2013. A semi-structured questionnaire and an informal interview were used to collect the data, and the material was treated using the Collective Subject Discourse analysis technique. The results show that the tutelary counselors' perceptions went through the recognition of a few peremptory aspects inherent to their practice, such as impotence in the face of the disturbing social scenarios to which they are exposed, along with the restriction of the scope of their action linked to structural barriers in the existing social protection networks, in addition to the population's low levels of adherence to their work process. They also reveal a deep-seated satisfaction in the developments of work they have done and that which has a positive impact on juvenile violence; this satisfaction, in turn, is considered as fuel for the development of their professional skills. The considerations this study captured confirm the presence of relevant gradations inherent in the relational process of the tutelary counselors in their work environment, supporting the recognition of the guiding parameters of the intersubjective relationship between the tutelary counselor and the social praxis.

Resumen Este estudio cualitativo introduce el tema de las representaciones de consejeros tutelares con el objetivo de ampliar la comprensión del universo de estos actores sociales y conocer sus implicaciones sobre la dinámica de su proceso de trabajo. El estudio se realizó en el municipio de Coronel Vivida, en el estado de Paraná, Brasil, en el año de 2013. Para la recolección de los datos se utilizó un cuestionario semiestructurado y entrevista informal, y el material se trató mediante la técnica de análisis del Discurso del Sujeto Colectivo. Los resultados muestran que las percepciones de los consejeros tutelares transcurrieron por el reconocimiento de algunos aspectos terminantes e inherentes a su praxis, como la impotencia frente a los perturbadores escenarios sociales a que están expuestos, atribuida a la restricción del alcance de su actuación vinculada a obstáculos estructurales de las redes vigentes de protección social y a la escasa adhesión de la población a su proceso de trabajo. Ponen de manifiesto también una satisfacción arraigada en los desdoblamientos laborales concluidos y en aquellos que infieren positivamente sobre la violencia infantil-juvenil, y esta satisfacción, a su vez, se considera combustible para el desarrollo de sus competencias profesionales. Las consideraciones aprendidas en el presente estudio ratifican la presencia de graduaciones relevantes, inherentes al proceso de relación del consejero tutelar en su ambiente de trabajo, corroborando el reconocimiento de parámetros orientadores de la relación intersubjetiva consejero tutelar y praxis social.

Resumo Este estudo qualitativo introduz o tema das representações de conselheiros tutelares com o objetivo de ampliar a compreensão do universo desses atores sociais e conhecer as suas implicações sobre a dinâmica do seu processo de trabalho. O estudo foi realizado no município de Coronel Vivida, Paraná, no ano de 2013. Para a coleta de dados foi utilizado questionário semiestruturado e entrevista informal, e o material foi tratado pela técnica de análise do Discurso do Sujeito Coletivo. Os resultados mostram que as percepções dos conselheiros tutelares transcorreram pelo reconhecimento de alguns aspectos terminantes e inerentes à sua práxis, como a impotência diante dos perturbadores cenários sociais a que são expostos, adjudicada à restrição do alcance de sua atuação vinculada a entraves estruturais das redes vigentes de proteção social e à baixa adesão da população ao seu processo de trabalho. Evidenciam também uma satisfação arraigada nos desdobramentos laborais concluídos e naqueles que inferem positivamente sobre a violência infanto-juvenil. Esse contentamento, por sua vez, é considerado combustível para o desenvolvimento de suas competências profissionais. As considerações apreendidas no presente estudo ratificam a presença de gradações relevantes, inerentes ao processo relacional do conselheiro tutelar em seu ambiente de trabalho, corroborando o reconhecimento de parâmetros norteadores da relação intersubjetiva conselheiro tutelar e práxis social.
THE YOUTH SOCIAL RUPTURE AND ITS INFERENCE IN THE REPRESENTATIONS OF TUTELARY COUNSELORS
LA RUPTURA SOCIAL INFANTIL-JUVENIL Y SU INFERENCIA EN LAS REPRESENTACIONES DE CONSEJEROS TUTELARES
Keywords: violence; child; teen; community-institution relations; violência; criança; adolescente; relações comunidade–instituição